Wear modelling in wheel–rail contact problems based on energy dissipation. (3rd April 2021) - Myśliński, Andrzej; Chudzikiewicz, Andrzej
ABSTRACT: This work is concerned with the numerical procedure to solve two-dimensional wheel-rail contact problem between a rigid wheel and an elastic-plastic rail lying on a rigid foundation. The contact phenomenon includes Coulomb friction, frictional heat generation as well as the wear of the contacting surfaces. The wear depth function appears as an internal variable in the non-penetration condition updating the gap between the worn surfaces of the bodies. Moreover the dissipated energy due to friction is calculated to evaluate the loss of material and to determine the shape of the contacting surfaces during the wear evolution process. This contact problem is solved numerically using the finite element method as well as the operator splitting approach and semi-smooth Newton method. The distribution of contact surface stresses and temperatures as well as the evolution of the shape of the contact surfaces and the wear depth are reported and discussed. GRAPHICAL ABSTRACT: UF0001